Persepsi Mahasiswa PTKI Provinsi Bengkulu dalam Moderasi Beragama dan Hadis-Hadis Toleransi - Karnedi, Rozian; Sodik, Achmad Ja’far; Kurniawan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This descriptive qualitative research describes in detail the perceptions of PTKI students in Bengkulu Province towards religious moderation, hadith tolerance, and its implementation. Pesantren students show a strong understanding, while non-Pesantren students show variations in interpretation. Despite these differences, all students overall support the religious moderation program and have a positive view of the hadith of tolerance. PTKI campuses in Bengkulu Province are actively involved in implementing religious moderation programs through moderation houses, integration of moderation values, and organizing discussion forums. In conclusion, this study highlights the diversity of perceptions among university students, while affirming the consistency of their support for religious moderation within PTKIs. The implementation of the program on campus reflects a commitment to promoting moderate understanding and acceptance among different groups or religions.Keywords: Perception, Religious Moderation, Tolerance